Respuesta :
the answer to the question is:
(x+1)(x+2)=0
x= -1, -2 for the real zeros
(x+1)(x+2)=0
x= -1, -2 for the real zeros
Answer:
x=-1
x=-2
Step-by-step explanation:
1. To solve this problem you can graph the quadratic function, as you can see in the graph attached.
2. You can estimate the solution of the quadratic function by observing two points where the parabola intersect the x-axis.
3. Keeping the the information above on mind, you can estimate that the solution is:
x=-1
x=-2
NOTE:
You can also find two numbers whose sum is 3 and whose product is 2. Then:
[tex](x+2)(x+1)=0\\x=-2\\x=-1[/tex]
![Ver imagen carlosego](https://us-static.z-dn.net/files/d78/7c97a5ad4c65c891f64f6081c5082d02.jpg)